450=600-500r

Simple and best practice solution for 450=600-500r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 450=600-500r equation:


Simplifying
450 = 600 + -500r

Solving
450 = 600 + -500r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '500r' to each side of the equation.
450 + 500r = 600 + -500r + 500r

Combine like terms: -500r + 500r = 0
450 + 500r = 600 + 0
450 + 500r = 600

Add '-450' to each side of the equation.
450 + -450 + 500r = 600 + -450

Combine like terms: 450 + -450 = 0
0 + 500r = 600 + -450
500r = 600 + -450

Combine like terms: 600 + -450 = 150
500r = 150

Divide each side by '500'.
r = 0.3

Simplifying
r = 0.3

See similar equations:

| f(x)=100x^2-100x-600 | | 7x-9=73 | | a+(-3)=2a+5 | | 151x+(1-x)(425)=255 | | 36=x-24 | | 8-3n=-8 | | Y-7=5(x+2) | | 4z^2-18=-z | | 2x+51=4x-5 | | 2v^2+8=104 | | 2(5-d)=2-4 | | 0.05x=0.056 | | 3(2x-1)=5(x+4) | | -14m-20m-4m-12m-19=15 | | 2(x-5)=46-6x | | 18x+63=27x+72 | | -9=-7+v | | 2x-9=63-7x | | 5x+(-2x-x+6)=18-(-7x-6-3x+24) | | x=1.21y+0.15x | | y=(-x)(-x)+6x-2 | | 10x+13=-20-7x | | (4x+5y)dx+(5x+6y)dy=0 | | 18x+63=27x-72 | | 25y^2+40y+16=28 | | 3(x)+2=11 | | 8a+8=24 | | 7-11z=-114 | | 40x+1.5=25x+3 | | 8y-y-3y= | | f(x)=6x^3-5x^2+6x+5 | | 2x+x+8=7 |

Equations solver categories